Reconstructing the history of deportation of Germans of Kalmykia - Okonova, Lyudmila V.; Lidzhieva, Irina V. (The New Research of Tuva, 2014)
During the World War II entire nation-ethnic groups had been politically repressed. Germans, whose ancestors settled in the Kalmyk steppes in the XIX century, had been among the first victims on the territory of Kalmyk ASSR. Article is an attempt to recreate the history of eviction of the German population from Kalmyk Autonomous Soviet Socialist Republic in 1941 on the basis of the first time revealed archival materials and memoirs of eyewitnesses of events.